Forum: equity in access to health care. Introduction Fórum: eqüidade no acesso aos serviços de saúde. Introdução - Claudia Travassos (Cadernos de Saúde Pública, 2008)
The Introduction outlines this issue's special Forum on equity in access to health care, including three Articles and a Postscript. The Forum represents a continuation of the debates raised during a seminar organized by the Oswaldo Cruz Foundation in the city of Rio de Janeiro, Brazil, in 2006, in collaboration with UNICEF, UNDP, World Bank, the WHO Special Program for Research and Training in Tropical Diseases, and the United Nations Research Institute for Social Development. The authors approach health care access and equity from a comprehensive and contemporaneous perspective, introducing a new conceptual framework for access, in which information plays a central role. Trust is proposed as an important value for an equitable health care system. Unethical practices by health administrators and health care professionals are highlighted as hidden critical aspects of inequities in health care. As a whole, the articles represent a renewed contribution for understating inequalities in access, and for building socially just health care systems. Nesta introdução apresenta-se o Fórum sobre eqüidade no acesso aos serviços de saúde, composto por três artigos e um posfácio. O Fórum representa uma continuidade das apresentações e debates ocorridos no seminário Equitable Access to Health Care and Infectious Disease Control: Concepts, Measurements and Interventions, organizado pela Fundação Oswaldo Cruz com a colaboração do Programa Especial de Pesquisa e Treinamento em Doenças Tropicais da Organização Mundial da Saúde (OMS) e o Instituto para o Desenvolvimento Social das Nações Unidas (UNIRISD), realizado na cidade do Rio de Janeiro, Brasil, em 2006. Acesso aos serviços de saúde e eqüidade são abordados nos artigos do Fórum de modo abrangente e contemporâneo. Um novo modelo teórico-conceitual, no qual a informação tem um papel central, é introduzido em um dos artigos. Em outro, confiança é apresentada como um valor importante para a construção de sistemas de saúde equânimes. Questões éticas nas práticas de administradores e profissionais de saúde são destacadas como aspectos geradores de iniqüidades pouco discutidos. No conjunto, os artigos apresentam novo conhecimento sobre os fatores geradores de iniqüidades no acesso aos serviços de saúde que representam uma contribuição à construção de sistemas de saúde mais justos.